Women Do Not Play Their Aces: The Consequences of Shying Away - Jörg Claussen; Eszter Czibor; Mirjam C. van Praag (Institute for the Study of Labor (IZA), 2015)
The underrepresentation of women at the top of hierarchies is often explained by gender differences in preferences. We find support for this claim by analyzing a large dataset from an online card game community, a stylized yet natural setting characterized by self-selection into an uncertain, competitive and male-dominated environment. We observe gender differences in playing behavior consistent with women being more averse towards risk and competition. Moreover, we demonstrate how "shying away" makes female players less successful: despite no gender gap in playing skills, women accumulate lower scores than men due to their relative avoidance of risky and competitive situations.
Keywords: D03; J24; M52; 330; gender; preferences; risk; competition; performance